ECONOMIC EVALUATION OF MULTIPLICATIVE EFFICIENCY ON THE BASIS OF GENERALIZED INDICATORS OF RESOURCE COMPONENTS IN TOURIST RECREATION ACTIVITIES - Mirzaev Abdullajon Topilovich (European Journal of Research Development and Sustainability, 2021)
In the article, studied the the basis of theoretical methods of economic evaluation of the multiplicative effect on the basis of generalized indicators of resource components in tourist recreation activities. Carried out multi-factor analysis in the EViews10 software package on the change in the influence of its main factor (resources) by taking the change in the number of users of services in the National tourist-recreation sector as the endogen factor. Based on the identified trend models based on the forecasts of the change in the number of recreants who will use tourist-recreation services in 2021-2025 years. Developed the structural model of evaluation of the effect of the multiplikative effect on the result of tourist-recreational activities and recommended to use in practice.